2002
DOI: 10.1177/216507990205000306
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Installing Overhead Ceiling Lifts

Abstract: The effectiveness of replacing floor lifts with mechanical ceiling lifts was evaluated in the extended care unit of a British Columbia hospital. Sixty-five ceiling lifts were installed between April and August 1998. Injury data were abstracted from injury reports for all staff musculoskeletal injuries (MSI) occurring in the unit during a 3 year period prior to installation and a 1.5 year follow up period. Descriptive statistics were calculated for injuries pre-versus post-installation. Rates were calculated as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The patient is suspended in a sling from an overhead track and this track allows patient care activities to be performed within the coverage area of the track. Ceiling lifts require less time for transfers than floor based mobile lifts; are stored overhead on a track and are a lucrative investment (Holliday, Fernie, & Plowman, 1994;Ronald et al, 2002;Villeneuve, 1998). One understudied area is the task of repositioning a patient in bed, as reflected in the associated injuries.…”
Section: Engineering Controlsmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient is suspended in a sling from an overhead track and this track allows patient care activities to be performed within the coverage area of the track. Ceiling lifts require less time for transfers than floor based mobile lifts; are stored overhead on a track and are a lucrative investment (Holliday, Fernie, & Plowman, 1994;Ronald et al, 2002;Villeneuve, 1998). One understudied area is the task of repositioning a patient in bed, as reflected in the associated injuries.…”
Section: Engineering Controlsmentioning
confidence: 99%
“…The patient is suspended in a sling from an overhead track and this track allows patient care activities to be performed within the coverage area of the track. Ceiling lifts require less time for transfers than floor based mobile lifts; are stored overhead on a track and are a lucrative investment (Holliday, Fernie, & Plowman, 1994;Ronald et al, 2002; Villeneuve, 1998 Few evidence-based studies agree that this critical task places caregivers at an increased risk of back injury due to high spinal loads. Although the two-person draw sheet repositioning technique has the lowest low back disorder risk, spinal loads were still high, thus increasing the risk of a back injury (Marras, Davis, Kirking, & Bertsche, 1999).…”
mentioning
confidence: 99%
“…Studies comparing floor lifts with ceiling lifts report fewer caregiver musculoskeletal injuries with use of the ceiling lift (Engst, Chhokar, Miller, Tate, & Yassi, 2005; Ronald et al, 2002). Laboratory studies indicated that ceiling lifts require half the effort of floor lifts (Nelson, 2005).…”
Section: Review Of Literaturementioning
confidence: 99%
“…This was substantiated by a reduction in compensation costs. After installation of ceiling lifts, cost savings in terms of compensation costs alone are estimated to produce payback within 6 years (Engst et al; Spiegel et al, 2002). Additional benefits include fewer lost work days, less severe injuries, and greater productivity.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Recently, Yassi et al (26) presented the logic behind integrating workplace resources across primary and secondary prevention approaches-a task which they described as "breaking down the solitudes". This proposal stemmed from the following observations: · An effective primary prevention initiative that was ergonomic in nature resulted not only in fewer injuries (primary prevention) in a hospital setting, but also in unexpectedly shorter durations of lost time after injury (secondary prevention) (27).…”
Section: An Optimal Effort To Reduce Workplace Injuries Illnesses Amentioning
confidence: 99%